Destruction of microparticles related to dusty plasma processes and possible technological applications - Morozova, T.I.; Kopnin, S.I.; Popel, S.I. (Вопросы атомной науки и техники, 2012)
A method of destruction of microparticles related to dusty plasma processes is discussed. The method includes the achievement of anomalously high dust particle charges, for which the destruction process of the particles starts. Technological applications of dust particle destruction can be associated with the separation of nano- and microscale monomineral fractions from polymineral microparticles, that is of practical interest for enhancement of the efficiency of development of low-grade deposits and reprocessing of ore dumps and tailings which contain a definite amount of noble metals in the form of fine-dispersed fractions.